Earnings Management, Audit Quality and Legal Environment: An International Comparison - Memis, Mehmet Unsal; Cetenak, Emin Huseyin (International Journal of Economics and Financial Issues, 2012)
This paper investigates the relationship between earnings management-audit quality and earnings management-legal system quality by using 1507 firms’ observations from listed companies in private firms across different 8 emerging countries. Consistent with previous research, differentiation between Big 4 and non-Big 4 audit firms are used as a audit quality proxy and discretionary accruals are used to measure the earnings management. According to the results, only for Brazilian and Mexican companies, there is significant relationship between the discretionary accruals and audit quality. For the other countries there is not significant relationship. Furthermore efficiency of the legal system helps decrease earnings management incentives. Along with results, the big four auditors do not constrain the earnings management incentives in every emerging country but effective legal system does. In this analysis we used other earnings management related variables like the size of the firms, leverage, lagged ROA of the firms which have loss in the previous year and Tobin Q as control variables. Keywords: Audit Quality; Earnings Management; Legal Enforcement JEL Classifications: M41; M42; M48